Normal viability and altered pharmacokinetics in mice lacking mdr1-type (drug-transporting) P-glycoproteins - Schinkel, Alfred H. (The National Academy of Sciences of the USA, 1997)
The mdr1-type P-glycoproteins (P-gps) confer multidrug resistance to cancer cells by active extrusion of a wide range of drugs from the cell. To study their physiological roles, we have generated mice genetically deficient in the mdr1b gene [mdr1b (−/−) mice] and in both the mdr1a and mdr1b genes [mdr1a/1b (−/−) mice]. In spite of the host of functions speculatively attributed to the mdr1-type P-gps, we found no physiological abnormalities in either strain. Viability, fertility, and a range of histological, hematological, serum–chemical, and immunological parameters were not abnormal in mdr1a/1b (−/−) mice. The high level of mdr1b P-gp normally present in the pregnant uterus did not protect fetuses from a drug (digoxin) in the bloodstream of the mother, although the protein did reduce drug accumulation in the adrenal gland and ovaries. Pharmacologically, mdr1a/1b (−/−) mice behaved similarly to the previously analyzed mdr1a (−/−) mice, displaying, for instance, increased brain penetration and reduced elimination of digoxin. However, both mdr1a and mdr1b P-gps contributed to the extrusion of rhodamine from hematopoietic progenitor cells, suggesting a potential role for the endogenous mdr1-type P-gps in protection of bone marrow against cytotoxic anticancer drugs. This, and the normal viability of mdr1a/1b (−/−) mice, has implications for the use of P-gp-blocking agents in cancer and other chemotherapy. mdr1a/1b (−/−) mice should provide a useful model system to further test the pharmacological roles of the drug-transporting P-gps and to analyze the specificity and effectivity of P-gp-blocking drugs.